2022
DOI: 10.1093/scan/nsac048
|View full text |Cite
|
Sign up to set email alerts
|

Incidental physical pain reduces brain activities associated with affective social feedback and increases aggression

Abstract: Physical pain may lead to aggressive behavior in a social context. However, it is unclear whether this is related to changes of social information processing. Thus, this study aimed to investigate the neural mechanisms underlying pain-induced aggression using functional magnetic resonance imaging. In the experiment, 59 healthy participants were recruited; 31 were treated with topical capsaicin cream (pain group), and 28 with hand cream (control group). Participants completed a social network aggression task, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, research should not be limited to physical experiences. Physical experiences (e.g., physical pain) implicitly play a similar role as social experiences (e.g., social pain) in affecting individuals' behavior [12]. Positive/negative experiences also include social experiences, such as success/failure and social acceptance/exclusion, which should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, research should not be limited to physical experiences. Physical experiences (e.g., physical pain) implicitly play a similar role as social experiences (e.g., social pain) in affecting individuals' behavior [12]. Positive/negative experiences also include social experiences, such as success/failure and social acceptance/exclusion, which should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unclear whether the conclusion that negative experiences promote cooperation is drawn from "shared negative experience" or "negative experience". Although an increasing amount of evidence shows painful experiences (a kind of negative experience) promoted cooperation [16,17], studies also found pain could increase aggressive behavior [12]. These inconsistent results suggest the possibility that moderating variables exist in the relationship between positive/negative experiences and cooperative behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, according to the General Aggression Model (GAM), aggression is associated with various social, cognitive, developmental, and biological factors [11]. However, previous studies have focused on the relationship between aggression and only one or two factors, including age [12,13], sex [10], chronic pain [14], low levels of physical activity [14,15], depression, anxiety [16][17][18][19][20], and marital status [21].…”
Section: Introductionmentioning
confidence: 99%